Research on the Development of Equitable Education in China from the Human Capability Perspective - Mingmei Li; Min Liu; Hejia Wang; Xiaohan Hong; Chen Wang (Education Sciences, 2023)
“Capability” is an important conceptual tool for addressing educational inequity (EI). This paper analyzes the existing limitations of developing educational equity in China from the human capital perspective and proposes the human capability approach as a way to improve it. This paper begins by a policy review on China’s education equity measures, revealing a troubling emphasis on resources allocation and a “top-down” governance. In response, we propose an actionable research approach as a means to improve multi-stakeholder collaboration in educational equity reform and to further the development of student capabilities. The study also presents a case study to illustrate the process of using “capability” and actionable research methods to promote educational equity, demonstrating the necessity and effectiveness. We also note that education inequality is a delicate and complicated topic that requires joint, flexible and innovative efforts.